The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1101/2020.04.24.059766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human CD8+T cells exhibit a shared antigen threshold for different effector responses

Abstract: T cells recognising cognate pMHC antigens become activated to elicit a myriad of cellular responses, such as target cell killing and the secretion of different cytokines, that collectively contribute to adaptive immunity. These effector responses have been hypothesised to exhibit different antigen dose and affinity thresholds, suggesting that pathogen-specific information may be encoded within the nature of the antigen. Here, using systematic experiments in a reductionist system, where primary human CD8 + T ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 48 publications
4
17
0
Order By: Relevance
“…We hypothesised that the absence of ligands for co-signalling receptors may account for this reduction in antigen discrimination. It has been shown that ligation of co-signalling receptors can greatly enhance antigen potency (42,44). Inclusion of recombinant ICAM1 (a ligand of LFA-1) or CD58 (the ligand to CD2) increased TCR downregulation ( Figure S4) and antigen potency ( Figure 3C) in this experimental system, consistent with previous reports using APCs (44,45).…”
Section: The Discrimination Power Of T Cells Is Dependent On Ligands supporting
confidence: 89%
See 1 more Smart Citation
“…We hypothesised that the absence of ligands for co-signalling receptors may account for this reduction in antigen discrimination. It has been shown that ligation of co-signalling receptors can greatly enhance antigen potency (42,44). Inclusion of recombinant ICAM1 (a ligand of LFA-1) or CD58 (the ligand to CD2) increased TCR downregulation ( Figure S4) and antigen potency ( Figure 3C) in this experimental system, consistent with previous reports using APCs (44,45).…”
Section: The Discrimination Power Of T Cells Is Dependent On Ligands supporting
confidence: 89%
“…Since APCs express ligands for many co-signalling receptors, we adopted a reductionist system (42,43) where recombinant pMHCs are presented on plates with or without ligands for co-signalling receptors before being used as stimulation surfaces for 1G4 T cell blasts ( Figure 3A).…”
Section: The Discrimination Power Of T Cells Is Dependent On Ligands mentioning
confidence: 99%
“…4D). This is consistent with a TCR-proximal mechanism of antigen discrimination (44,45) that has a similar threshold for different T cell responses (46)(47)(48).…”
Section: The Discrimination Power Is Similar For Different T Cell Ressupporting
confidence: 84%
“…We found a number of studies, including previous work from our laboratory, that relied on reductionist systems where recombinant pMHC is presented in isolation on plates (e.g. biotinylated pMHC immobilised on streptavidin-coated plates (10,11,47,53,54)). To assess the impact of artificial presentation, we quantified discrimination powers from these studies finding that α decreased significantly from 2.0 on APCs to 0.93 when presented on artificial surfaces (Fig.…”
Section: The Discrimination Power Is Similar For Different T Cell Resmentioning
confidence: 99%
“…There is accumulating evidence that genetic background, private TCR specificities and immunological history are key factors contributing to the final outcome of antigen exposure-whether to confer protective immunity or induce damaging immunopathology (25,38,39). It is of note that peptide recognition is not a simple on/off event, and that the same T cell can respond in different ways to modified peptides, by for example, pMHC affinity and dose thresholds (40,41), co-stimulatory molecules (42), and hierarchical organization of thresholds (43,44).…”
Section: Predicting Cross-recognition Potential Of T Cell Receptorsmentioning
confidence: 99%